Efektivitas Implementasi Program Beras Sejahtera (Rastra) Di Kelurahan Konawe Kecamatan Kusambi Kabupaten Muna Barat - Serlin, Serlin; Qomariyah, Erni; Manguntara, La (Universitas Halu Oleo, 2021)
The purpose of this study is to describe the effectiveness of the implementation of the Rastra program in Konawe Village, Kusambi District, Muna Barat Regency. Data collection techniques using observation, interview and documentation techniques. The data analysis technique in this research is using qualitative descriptive analysis techniques. There were 8 informants in this study consisting of Rasmin S.Pt as the head of the village head, La Dae as a functional position, Wa Haliya SP as the secretary of the village head, La Salati as the head of environment II, 3 people who received rastra and I as a community member. who are not rstra recipients.The results of this study indicate that the effectiveness of the implementation of the Rastra program in the Konawe village, Kusambi district, West Muna district. In general, it does not fully refer to the provisions of the 6T indicator, namely right on target, right amount, right price, right time, right quality and right administration. Because in the distribution of literature in the field it only fulfills 2 indicators, namely the right amount and the right price. Meanwhile, the accuracy of targeting is still not quite right because there are still people who receive rastra whose economic conditions are already quite good but are still given rice assistance, then punctuality means that there are often delays in distribution every month. While the accuracy of quality is still not good because many people still get rice that is not bad enough. Meanwhile, administrative accuracy has not been achieved because the income for the recipients of this rastra aid should be families that really meet the criteria, namely families with low economic income. However, the fact remains that there are well-off families who are registered as recipients of rice rastra assistance.